Immunity status and expression of molecular markers (ICAM-1, CD5, CD25, CD95) on lymphocytes of patients with recurrent anterior uveitis complicated by macular edema - Храменко, Наталія Іванівна; Коновалова, Наталія Валеріївна; Усов, Володимир Якович; Величко, Людмила Миколаївна; Богданова, Олександра Вікторівна (My University, 2023)
Background Treatment of macular edema in uveitis is a key goal of treatment, because this complication remains a potential therapeutic problem for specialists. Material and methods Examination was carried out in 1–2 groups — 50 persons with uncomplicated recurrent anterior uveitis (AU) in the stage of relapse or remission — and 3–4 groups — 26 persons with recurrent AU complicated by uveitic macular edema (UME) in the stage of relapse or remission of AU. Control group — 27 healthy volunteers. All patients underwent an ophthalmologic examination, using OCT (Spectralis HRA + OCT (Heidelberg Engineering)). The state of cellular and humoral immunity and the expression of activation markers on blood lymphocytes in all patients were assessed. An immunohistocytochemical analysis using monoclonal antibodies (the peroxidase–anti-peroxidase method) was employed to assess the expression of lymphocyte activation markers. The monoclonal antibody panel (MCAP) for immunophenotyping included antibodies reacting with CD5, CD54 (ICAM-1), CD25, and CD95 (FAS) antigens. Immunophenotyping was performed using immunohistochemistry. Results In the patients with AU + UME, the parameters of the T-cell link of the immune response were increased and the parameters of humoral immunity (CD19, IgA, IgG) were decreased in comparison with the uncomplicated AU patients. The absolute and relative numbers of natural killer cells in the peripheral blood were higher, and the relative numbers of phagocytic neutrophils were lower in the group of anterior uveitis with UME than in uncomplicated AU. The absolute and relative expression levels of ICAM-1 (CD54) and the absolute expression level of CD5 on peripheral blood lymphocytes were increased in relapse at patients with AU + UME compared with uncomplicated AU. The expression levels of CD25 and CD95 were not different in these groups. Conclusion Activation of cellular immunity markers ICAM-1 and CD5 seems to play a role in uveitic macular edema. The expression levels of CD25 and CD95 were not significantly different in these groups.